2008
DOI: 10.1038/sj.bjc.6604836
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot evaluation of a complex intervention to improve experienced continuity of care in patients with cancer

Abstract: High experienced continuity of care in patients with cancer is associated with lower needs for care, better quality of life and better psychological outcomes. We developed and evaluated an intervention to improve experienced continuity. The intervention, consisted of (1) a 17-item patient-completed continuity assessment; (2) feedback to clinical nurse specialists and action to address the needs identified. Multidisciplinary team meetings and oncology outpatient clinics were observed, and patients and staff wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 10 publications
2
42
0
2
Order By: Relevance
“…Four of the seven RCTs reported that allocation was concealed when eligibility was being assessed [29–32]. …”
Section: Resultsmentioning
confidence: 99%
“…Four of the seven RCTs reported that allocation was concealed when eligibility was being assessed [29–32]. …”
Section: Resultsmentioning
confidence: 99%
“…These additional team members may be physically present at the MDC meeting or available for consult. This ensures that the patient is informed and guided during and after treatment, from inpatient status to outpatient status, moving patient care prospectively (12,16). Table 1 summarizes the ways in which the MDC team has differed historically from tumor boards, although in practice these distinctions can sometimes be blurred and models can blend various dimensions (17).…”
Section: Treatment Processes and Teammentioning
confidence: 99%
“…We noted knowledge gaps about issues such as coordination of care, follow up and survivorship (King et al, 2009;Schmidt-Hansen, Baldwin & Hasler, 2012;Surapaneni, Singh, Rajagopalan, & Hageboutros, 2012). Conducting an in-depth review of the prevention and screening literature was beyond the scope of our research.…”
Section: Variations In Treatments Offeredmentioning
confidence: 99%